THE ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN SMEs: CASE STUDY OF THE TURISTRELA GROUP - Mário Franco; Bruna Dias; Carla Pereira (Enlightening Tourism: A Pathmaking Journal)
The aim of this study concerns the role of the application/adoption of Information and Communication Technologies (ICT) in small and medium-sized enterprises (SME). This investigation identifies the factors influencing the adoption of ICT in SMEs and the benefits and/or costs for this type of firm. Based on one SME – Turistrela, the case study method was chosen, with the data collection instruments being the interview and documentary analysis. Based on the results obtained, ICT were found to improve all processes and communication in the firm’s various departments, as well as the connection with outside, from within the region to other countries. As ICT are already implemented worldwide, these have become fundamental for the success of Turistrela. The empirical evidence also shows that without these technologies, rapid communication and the processing and analysis of information would be difficult, and this type of activity in the selected firm would become more expensive and less effective.